2009
DOI: 10.1590/s0044-59672009000400002
|View full text |Cite
|
Sign up to set email alerts
|

Inoculação das sementes e adubações nitrogenada e molíbdica do feijoeiro-comum, em Rolim de Moura, RO

Abstract: RESUMOO objetivo deste estudo foi avaliar o desempenho do feijoeiro-comum (Phaseolus vulgaris L) em função da inoculação de sementes com Rhizobium tropici e das adubações nitrogenada e molibdica. Utilizou-se o delineamento em blocos casualizados, com quatro repetições, em arranjo fatorial 2x2x2, constituindo-se das combinações de ausência e presença de inoculação de sementes, da adubação molíbdica e da adubação nitrogenada. A inoculação das sementes foi imediatamente antes da semeadura com inoculante turfoso c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
4
11
1
8
Order By: Relevance
“…The root dry weight (RDW) showed no significant differences in the treatments of both crop seasons (Table 1), indicating no correlation of this variable with the SDW in this experiment, confirming the results of Valadão et al (2009), who found similar results in common beans. Table 1.…”
Section: Resultssupporting
confidence: 85%
“…The root dry weight (RDW) showed no significant differences in the treatments of both crop seasons (Table 1), indicating no correlation of this variable with the SDW in this experiment, confirming the results of Valadão et al (2009), who found similar results in common beans. Table 1.…”
Section: Resultssupporting
confidence: 85%
“…Contudo, no presente trabalho, a utilização em conjunto das duas fontes de N, adubação mineral, com 20 kg ha -1 de N no plantio e 40 kg ha -1 de N na pré-floração, e inoculação com rizóbios, contribuiu para obtenção de maior massa seca de parte aérea no tratamento adubado e inoculado. Para massa seca de raiz não foi verificado efeito entre os tratamentos, nas duas épocas de cultivo, o que também foi observado por Valadão et al (2009).…”
Section: Numero De Nódulosunclassified
“…On the other hand, the application of a small dose of N at planting, together with inoculation with efficient Rhizobium spp. strains and foliar fertilization with Mo can be important tools for increasing bean yields and profitability for farmers (Vieira, Ronzelli Júnior, Daros, Koehler, & Prevedello, 2000;Valadão et al, 2009;Albuquerque, Pegoraro, Vieira, Amorim, & Kondo, 2012). However, the low number of studies does not allow reliable conclusions, mainly related to Mo application.…”
Section: Introductionmentioning
confidence: 99%